Challenges for Teachers in Developing their Teaching Professionalism: A Case Study of Secondary School in Makassar, Indonesia - Hasan Tanang; Muhammad Djajadi; Baharin Abu; Mahani Mokhtar (Intelektual Pustaka Media Utama, 2014)
Identifying challenges for teachers in developing their professionalism in teaching to improve students’ learning outcomes. The focus was addressed on the development of teaching professionalism in improving knowledge and skills of Junior High School teachers in Makassar Indonesia. This study employed qualitative methods through a case study to identify the barriers of professionalism in teaching. 36 samples for open-ended questionnaire and nine of them are selected purposively to be interviewed. The data was analyzed by coding based on themes related to constraints in teaching management. The results showed four obstacles experienced by teachers in developing their professionalism, namely constraints on textbooks and student worksheets, school laboratory usage, ICT-based media, and the students themselves. The identification could encourage the community and parents support to finance the development of professionalism in teaching and to help the teachers work effectively